Upaya Penanganan Masalah Konstipasi Ibu Hamil Trimester III - WIDYASARI, SHINTA, Winarsih Nur Ambarwati, S.Kep., Ns., ETN., M.Kep (2017)
Result of WHO in 2016 with patients of stroke, reaching 15 million people worldwide every year her (3.5 million women and 3.1 million men). Stroke is a disorder of the central nervous system function that occurs suddenly can be a brain blood vessel blockage or rupture of blood vessels of the brain and is usually caused by impaired blood vessel in the brain. One of the problems of nursing that requires further treatment, namely physical mobility barriers, for stroke patients will feel the loss of power on one of the limbs. The author can provide an overview of nursing care to patients in Improving Stroke Physical Mobility with Haemorrhagic Stroke. The method used in the writing of scientific papers that dekskriptif with case study approach in stroke patients on 6 February 2017 to 8 February 2017. After the act of nursing for 3x24 hours in stroke patients with some monitoring vital signs, review the patient's ability to mobilize, teach families and patients about exercise range of motion (ROM), assist and help when the patient mobilization, teach patients how to change the position and provide assistance if needed, help the patient provide health education to patients' families about the importance of range of motion (ROM). Diagnosis physical mobility constraints are resolved in part, continued intervention such as ROM exercises, often change the position of patients. Conclusion: physical mobility constraints nursing problems resolved partially, thus requiring further treatment so that outcomes can be achieved.